ANALISIS KESULITAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI PESERTA DIDIK DI SEKOLAH DASAR - Inggriyani, Feby; Anisa Pebrianti, Nur (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
ABSTRACT This descriptive analysis study aims to determine the ability to write descriptive essays in fourth grade students at SDN Griya Bandung Indah. The data analysis method in this study used qualitative descriptive analysis. Data collection techniques used in this study were documentation and interviews. The average value of the ability to write descriptive essays is 54.6 with less qualifications. The percentage of suitability of the title with the theme of the essay is 66% or equal to 20 students including the very good/good category, the percentage of neatness of writing and accuracy of diction is 73.3% or equal to 22 people who are still not neat in their writing and choice of words/diction , the percentage of essay writing structure is 56.7% or equal to 17 people including very good/good category, percentage of suitability of ideas with essays is 63.3% or equal to 19 people who are still lacking in suitability of ideas with essays, and percentage of spelling usage In general, the Indonesian language is 87% or equal to 26 people, including the category of lacking in writing capital letters and using punctuation marks in accordance with general Indonesian spelling guidelines. The obstacles faced by students are that they find it difficult to express their ideas into words/sentences, this is due to the lack of interest of students in reading and the lack of students to get used to the practice seriously. Factors that influence learning difficulties in writing descriptive essays are intelligence, interest in learning, attitudes and behavior towards lessons, motivation, learning standards, factors from educators who use inappropriate media, methods, and learning tactics.